Hodnocení finanční situace podniku a návrhy na její zlepšení - Pešková, Helena (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Bakalářská práce se zaměřuje na hodnocení finanční situace společnosti Microtex a.s. v letech 2015-2019 za pomoci vybraných finančních ukazatelů a metod. Dané metody a ukazatele jsou popsány v teoretické části a následně interpretovány v části praktické. V této části je také popsána analyzovaná společnost a představen konkurenční podnik. Poslední část představuje na základě výsledků finančních ukazatelů návrhy vedoucí ke zlepšení finanční situace společnosti.

The bachelor thesis is focused on the evaluation of financial situation of the company Microtex a.s. in years 2015-2019 using financial indicators and methods. These methods and incicators are described in the theoretical part of this thesis and later on they are interpreted in the practical part of this work. In the practical part it is also analyzed the company and it is described the competing company as well. The final part presents the suggestions for improvement of the company’s situation based on the results of the financial indicators.
Evaluation of the Financial Situation of the Company and Proposals for its Improvement
Keywords: finanční analýza; rozvaha; výkaz zisku a ztrát; finanční ukazatele; rentabilita; hodnocení; finanční situace; optimalizace nákladů; navýšení zisku; financial analysis; balance; profit and loss statement; profitability; evaluation of the financial; situation; cost optimalization; increase profits